A passionate travel to mind green turtles-Unpacking the complexity of visitors' green behaviour - Akhshik, Arash; Ozturen, Ali; Rezapouraghdam, Hamed (Wiley, 2021)
The current studies in the tourism-environmental domain often take a reductionist approach towards the complex issue of human behaviour that is criticized for its shortcomings. Therefore, to fill this gap, the authors developed and tested a theoretical model drawing on the complexity theory with emerging concepts, that is, dualistic-passion paradigm, and mindfulness notion to predict the potential source of pro-environmental behaviour. Following Fuzzy set qualitative comparative analysis (fsQCA) of a sample from visitors to marine turtles in Cyprus, the study found seven unique causal recipes that lead to a high level of pro-environmental behaviour. Implications and guidelines for further research are discussed.
Keywords: Alagadi Turtle Beach; fsQCA; mindfulness; passion; pro-environmental behaviour